35 Raising the suspicion of adult congenital heart disease (achd) in symptomatic patients without abnormal initial echocardiographic findings; a case report. (6th June 2022) - Hussein, Ahmed; Kiberu, Yusuf; Sanders, Roy; Ozyigit, Tolga
Abstract : Introduction: Patients with adult congenital heart disease (ACHD) often initially present to their local hospital with cardiovascular symptoms such as dyspnoea and palpitations. Most patients undergo an echocardiogram as part of their initial investigations for more common aetiologies such as valvular heart disease, arrhythmias, and cardiomyopathies. The possibility of ACHD is often to the causes above therefore despite a systematic segmental approach, it is often not thoroughly considered when performing the initial echocardiogram. This can delay diagnosis and management.We report a case of a missed PDA in a 71-year-old female presenting with shortness of breath and palpitations for 10 years.MethodA 71-year-old female with no significant medical history presented with shortness of breath and palpitations. She had had these symptoms for over 10 years with the initial presentation at the age of 61. She had previously been investigated with an echocardiogram which was unremarkable (see results) as well as no evidence of arrhythmia on Holter monitoring. Her thyroid function and electrolytes were all unremarkable.On re-review, we subsequently repeated the echocardiogram and Holter monitor in view of worsening palpitations. We compared the images obtained on the echocardiograms to identify any discrepancies. Results: Echo in 2013: Non dilated LV with good systolic function, grade 2 diastolic dysfunction, mildly thicken aortic valve with mild AR. LVEDV 102 ml, poor image quality for LAVI measurements. Echo 2021 (Figure 1): Normal LV size, wall thickness and systolic function. Left atrium dilated, moderate AR and aortic root dilatation. Patent ductus arteriosus. LVEDV 117.05 ml, LAEDVInd 54.44 ml/m2ECG 2021: AF (Figure 2)DiscussionPatent ductus arteriosus (PDA) represents a communication between the aorta and the pulmonary artery with a left-right shunt at onset. PDAs usually close spontaneously within 24–48 hours after birth and are rarely encountered in adulthood, often found incidentally. Uncorrected PDAs can lead to left atrial and ventricular dilatation with symptoms of congestive cardiac failure such as in our patient above who also subsequently developed atrial fibrillation.It is therefore important that the initial scan in these patients comprehensively assess for ACHD. The views obtained in the initial scan were suboptimal. The subsequent diagnostic scan was performed by an experienced cardiac physiologist with better image quality on the same patient.It is reported that frequently the skill of the sonographer and the completeness of the study determines the accuracy of an echocardiographic diagnosis (1). Some authors have highlighted the importance of scan conditions such as the patient`s size, compliance, associated co-morbidities as well as operator experience. Benavidez et al found that the presence of an experienced cardiac physiologist or imaging cardiologist during certain situations improved diagnostic accuracy, for example in our patient above where despite a normal echocardiographic study, a cardiac cause of symptoms was still a high possibility. (2) Conclusion: Diagnosing ACHD in symptomatic patients requires clinical suspicion and experience for an appropriate initial echocardiogram. ACHD suspicion therefore should prompt a referral to a specialist ACHD team with the appropriate level of experience. Conflict of Interest: none